2022
DOI: 10.1186/s12912-022-00897-z
|View full text |Cite|
|
Sign up to set email alerts
|

Use of simulation to improve nursing students’ medication administration competence: a mixed-method study

Abstract: Background Medication administration errors are among the most important adverse events in healthcare systems. To minimise the risk of this occurring, nursing training programmes should emphasise the overriding priority of patient safety. In this respect, simulation can be a valuable resource in teaching procedures, for patient safety in general and safe medication administration in particular. In this study, we evaluate the use of a simulation-based activity for students to acquire skills in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported an error in the given name and family name designation, the given name and family name need to be interchanged.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the given name and family name designation, the given name and family name need to be interchanged.…”
mentioning
confidence: 99%